Pengaruh Indekspembangunan Manusia (IPM) Dan Tingkat Pengangguran Terhadap Pertumbuhan Ekonomi Kabupaten/Kota Di Kalimanatan Barat - B01110044, MARLINGGA LINGKUI LINGKUI (Jurnal Pembangunan dan Pemerataan, 2016)
Skripsi with a title â€œ influence human development index (hdi) and unemployment rate on economic growth/city district in west kalimantanâ€. The purpose of this research is to analyze the effects of human development index (hdi), unemployment rate on economic growth/city district in west borneo.This research using quantitative methods, namely by processing secondary data and analysis was conducted towards an object of this research according to research purposes. The data used was secondary data the period 2010-2013 originating from publication statistics west borneo province.From test t, human development index (hdi) influential positive and significant on economic growth of 1.156826, and unemployment have negative effects and significantly to economic growth rate of -0.228689 on growth/city in west kalimantan. Based on the results of the f that human development index (hdi) and unemployment significant on economic growth/city district in west borneo.Keywords: â€œhuman development index (hdi), unemployment and economic growthâ€.Pemban